The impact of performance management on employee engagement in China - JIANG, LIWEN (2020)
Abstract Purpose Performance management is crucial for organizations to improve competitive advantages. The increasing number of companies improve their performance management systems to enhance employee engagement, thereby increasing organizational performance. The aim of this paper is to explore the relationship between performance management and employee engagement in China.